Hesitant Fuzzy Compactness and Hesitant Fuzzy Regularity in Hesitant Fuzzy Topological Spaces (European Journal of Pure and Applied Mathematics, 2023)
We define hesitant fuzzy maximal open cover to establish hesitant fuzzy m-compactness and discuss its properties. Further we obtain few more results on hesitant fuzzy minimal c-regular and minimal c-normal spaces. We have proved that a hesitant fuzzy Haussdorff m-compact space is hesitant fuzzy minimal c-normal.
Keywords: Hesitant fuzzy minimal open, hesitant fuzzy maximal open cover, hesitant fuzzy m-compact, hesitant fuzzy minimal c-regular.